EDUCATIONAL STATUS OF WOMEN SLUM DWELLERS IN KOLKATA MUNICIPAL CORPORATION: A CASE STUDY ON SELECTED WARDS - Basu, Kamalika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The educational status of women living in urban slums is a critical indicator of social development, yet it remains an underexplored area in the context of Kolkata Municipal Corporation (KMC). This study examines the educational attainment, challenges, and socio-economic factors influencing the education of women slum dwellers in selected wards of KMC. Adopting a mixed-methods approach, the research utilizes primary data collected through surveys and interviews with 200 women from 10 selected wards, complemented by secondary data from government and non-governmental reports. The findings reveal stark disparities in educational attainment, with a significant proportion of women possessing only basic literacy or no formal education. Key barriers include financial constraints, early marriage, lack of access to educational infrastructure, and socio-cultural norms that de-prioritize women’s education. The study also highlights the role of community-based initiatives and government programs in fostering educational opportunities, albeit with limited outreach and effectiveness. The findings also reveal that while literacy rates have improved in recent years, the majority of women have limited access to higher education or skill development programs. Economic constraints, gender biases, lack of infrastructural facilities, and the competing demands of household responsibilities emerged as major obstacles to educational attainment. Additionally, the study highlights variations in educational status across the selected wards due to differences in socio-economic conditions and proximity to educational institutions. This paper underscores the critical need for targeted interventions, such as inclusive education policies, community-based awareness programs, and infrastructural improvements, to address these disparities. By providing a nuanced understanding of the educational challenges faced by women in slum areas, this research aims to contribute to the discourse on urban poverty and gender inequality.